Effect of fertilization and arbuscular mycorrhizal fungal inoculation on antioxidant profiles and activities in Fragaria ananassa fruit. (10th October 2018) - Parada, José; Valenzuela, Tamara; Gómez, Francisca; Tereucán, Gonzalo; García, Susana; Cornejo, Pablo; Winterhalter, Peter; Ruiz, Antonieta
Abstract: Background: The main methods used to increase the yield and quality of strawberry fruit produced in acidic soils with low P availability include root colonization by arbuscular mycorrhizal (AM) fungi and adjusting the type of P supplementation by means of traditional (TF) or organic (OF) fertilization, and adjusting nutrient doses. In this study, the antioxidant properties of strawberry fruit were evaluated under different treatments of fertilization (TF or OF) and different doses of P supplied at planting (0, 50 or 100% of the agronomic recommendation) and in the presence or absence of AM fungus as a bioinoculant. Results: Fruits without fertilization treatments and with TF presented with higher anthocyanin concentrations. In general, higher values were obtained without AM colonization. However, spectrophotometric tests showed the highest activity and concentration in the AM‐inoculated treatments. It is likely that phenolic compounds other than anthocyanins are present in the extracts. These other compounds could not be identified by the method used but could be detected by the Folin–Ciocalteu method. Conclusion: This study provides information that allows for improvements in strawberry fruit quality by agronomic management, with a potential beneficial effect on the health of consumers. © 2018 Society of Chemical Industry